2018
DOI: 10.1371/journal.pone.0208765
|View full text |Cite|
|
Sign up to set email alerts
|

Diatom evidence of 20th century ecosystem change in Lake Baikal, Siberia

Abstract: Lake Baikal has been experiencing limnological changes from recent atmospheric warming since the 1950s, with rising lake water temperatures, reduced ice cover duration and reduced lake surface-water mixing due to stronger thermal stratification. This study uses lake sediment cores to reconstruct recent changes (c. past 20 years) in Lake Baikal’s pelagic diatom communities relative to previous 20th century diatom assemblage records collected in 1993 and 1994 at the same locations in the lake. Recent changes doc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Among other common driving factors, such as light availability, wind speed, turbidity, and nutrient availability, or a combination of these factors, diatom shifts were mainly related to the response of Lake Bolshoe Toko to increasing air temperature, associated with shorter ice cover and longer summer thermal stratification. Influence of recent atmospheric warming on planktonic diatoms, caused by stronger thermal stratification, has also been observed in Lake Baikal (Roberts et al 2018) and in lakes of western Russia (Solovieva et al 2008).…”
Section: Diatom Responses To Post-industrial Warming Inferred At Diffmentioning
confidence: 83%
“…Among other common driving factors, such as light availability, wind speed, turbidity, and nutrient availability, or a combination of these factors, diatom shifts were mainly related to the response of Lake Bolshoe Toko to increasing air temperature, associated with shorter ice cover and longer summer thermal stratification. Influence of recent atmospheric warming on planktonic diatoms, caused by stronger thermal stratification, has also been observed in Lake Baikal (Roberts et al 2018) and in lakes of western Russia (Solovieva et al 2008).…”
Section: Diatom Responses To Post-industrial Warming Inferred At Diffmentioning
confidence: 83%
“…~9000 copies in Tetrahymena thermophila (Ward et al ., 1997)), such that their relative abundance in term of cells is certainly much lower. Although diatoms (Bacillariophyta, Ochrophyta), several of them considered endemic, are well known in Lake Baikal plankton (Moore et al ., 2009; Zakharova et al ., 2013; Bashenkhaeva et al ., 2015; Roberts et al ., 2018; Mikhailov et al ., 2019b), they represented only 6.1% ochrophyte reads distributed in 64 OTUs. Optical microscopy on board showed that diatoms were numerous, but their long frustules prevented most of them from being retained in the analysed plankton fraction.…”
Section: Resultsmentioning
confidence: 99%
“…That diatom communities are very dynamic, they respond quickly to disturbance, but they also recover. These observations may hold insights into the unfolding changes occurring in recent decades; for example the decline in heavily silicified endemic taxa and the growth of the cosmopolitan S. acus (Roberts et al, 2018). That this https://doi.org/10.5194/cp-2020-70 Preprint.…”
Section: Discussionmentioning
confidence: 99%
“…Here we investigate the relationship between diatom diversity and the stability of ecosystem functioning in Lake Baikal, an ancient lake with a long continuous record which, unlike many other large lakes, only shows limited evidence of human perturbation (Hampton et al 2018;Roberts et al 2018), restricted to its coastline (Kravtsova et al 2014;Timoshkin et al 2016). We focus on aquatic productivity as a measure of ecosystem function, because of the direct link between diatoms and primary production in the modern lake (Kozhova and Izmest'eva 1998).…”
Section: Introductionmentioning
confidence: 99%